The Better Route to Global Tax Coordination: Gradualism or Multilateralism? - Kai A. Konrad; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2018)
In the context of international tax coordination incomplete information is one of the well-known frictions that can lead to bargaining failure and might explain a lack of observed coordination. We consider international negotiations about tax coordination under complete and incomplete information. We identify the conditions for multilateral negotiations to be more likely to be successful than gradual/sequential negotiation approaches and compare different routes of sequential bargaining. Under plausible conditions, full-scale global coordination is least likely to emerge if the negotiations take place sequentially, and if the negotiations with the most unpredictable country take place last.
Keywords: H25; H77; F52; F55; 330; tax competition; tax cooperation; multilateral negotiations; sequential negotiations; ultimatum bargaining; acceptance uncertainty